BASICS Phase I Final Report - Bentley, J.W.; Nitturkar, H.; Friedmann, M.; Thiele, Graham (International Potato Center, 2020)
The Building a Sustainable, Integrated Seed System for Cassava in Nigeria (BASICS) was a five-year (2016-2020) project, funded by the Bill & Melinda Gates Foundation that worked to strengthen all components of the cassava seed value chain. The project was led and implemented by the CGIAR program on Roots, Tubers and Bananas in partnership with International Institute of Tropical Agriculture (IITA), National Agricultural Seeds Council (NASC), National Root Crops Research Institute (NRCRI), Catholic Relief Services (CRS), Context Global Development (CGD), and Fera Science Limited (Fera).